Correction: Kazmi et al. Formulation and Evaluation of Kaempferol Loaded Nanoparticles against Experimentally Induced Hepatocellular Carcinoma: In Vitro and In Vivo Studies. Pharmaceutics 2021, 13, 2086 - Imran Kazmi; Fahad A. Al-Abbasi; Muhammad Afzal; Hisham N. Altayb; Muhammad Shahid Nadeem; Gaurav Gupta (MDPI AG, 2022)
In the original publication [...]